PENGARUH PENDIDIKAN DAN PELATIHAN, KOMUNIKASI, DAN KOMPETENSI TERHADAP KINERJA PENYULUH KB ASN PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN SITUBONDO - Gita Eka Febryana; Mohammad Yahya Arief; Triska Dewi Pramitasari (Fakultas Ekonomi dan Bisnis, 2026)
This study aims (1) to determine the effect of leadership style, competence and motivation partially on state civil apparatus’ work productivity (2) to determine the effect of leadership style, competence and motivation simultaneously on state civil apparatus’ work productivity (3) to determine between leadership style, competence and motivation are the most dominant influence on the state civil apparatus’ work productivity. The method used in this study is a probability sampling method. The result of this research is multiple linear regression equation Y = 2,895E-17 + 0.298X1 + 0.227X2 + 0.476X3 + e. Partially the leadership style has a significant positive effect with a tcount value of 2,683 ttable of 2.011, competence has a significant positive effect with a tcount of 2.498 ttable of 2.011 and motivation has a significant positive effect with a tcount of 4,228 ttable of 2.011. Simultaneously the leadership style, competence and motivation affect the state civil apparatus’ work productivity with an Fcount of 30,966 Ftable of 2.80. The dominant variable in this study is the motivation with a value of 4.228.